An Analysis of Deixis in Avicii’s Song Lyric - Satyadewi, Ni Putu Melati; Ayomi , Putu Nur; Sulatra , I Komang (Journal of Language and Applied Linguistics, 2023)
Deixis is an expression in language used to point who, when, and where based on the context in the utterance. This study focuses with the deixis found in Avicii’s selected song lyrics. Therefore, this study aimed to find out the types of deixis used in Avicii’s song lyrics selected songs and analyze the context of situation of the deixis found in the Avicii’s song lyrics. The data were analyzed in descriptive qualitatively method and used eight song lyrics by Avicii. The theory used in analyzing the data are the theory proposed by Levinson (1983: 62-85) that discusses about the types of deixis and the theory from Halliday and Hassan (1985) which was used to analyze the context situation of deixis. Through the analysis, it shows that all types of deixis are found in the eight song lyrics by Avicii. They consist of person deixis, spatial deixis, temporal deixis, social deixis, and discourse deixis. The result of this study shows that person deixis is the most frequently used types of deixis. Deixis is very useful for language users in order to accurately process the meaning of utterances.